\[

\begin{align}

\nabla \times \vec{\mathbf{B}} -\, \frac1c\, \frac{\partial\vec{\mathbf{E}}}

{\partial t} & = \frac{4\pi}{c}\vec{\mathbf{j}} \\

\nabla \cdot \vec{\mathbf{E}} & = 4 \pi \rho \\

\nabla \times \vec{\mathbf{E}}\, +\, \frac1c\, \frac{\partial\vec{\mathbf{B}}}{\partial t} & = \vec{\mathbf{0}} \\

\nabla \cdot \vec{\mathbf{B}} & = 0

\end{align}

\]

\[

\begin{align}

\sum_{k=0}^n a

\end{align}

\]

\[

\displaystyle \sum_{j=1}^n a_j = \left({a_1 + a_2 + \cdots + a_n}\right)

\]

\[

\displaystyle \sum_{k=m}^n f_k \left({g_{k+1} - g_k}\right) = \left({f_{n+1} g_{n+1} - f_m g_m}\right) - \sum_{k=m}^n \left({f_{k+1}- f_k}\right) g_{k+1}

\]

## No comments:

## Post a Comment